2023
DOI: 10.3390/met13081484
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Thermal Field and Performance Study on H13 Die Steel-Based Wire Arc Additive Manufacturing

Yu Zhu,
Jufang Chen,
Xiaoping Li

Abstract: In order to explore the relationship between welding thermal cycles and the thermal field during the repair process of dies, a numerical simulation software (SYSWELD) was employed to construct a thermo-mechanical coupled model. The influence of various inter-layer cooling times was investigated on heat accumulation, residual stress, and deformation of the repaired component. The results showed that the numerical simulation results agreed well with experimental data. The temperature within the cladding layer gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, for a more detailed analysis, Figure 8a shows the microstructure at the interface for coating C1, highlighting the presence of martensite and austenite. Prior research has found that high Ni and Mo content stabilizes austenite during solidification, leading to the formation of austenite [63]. Martensite formation at the interface zone is attributed to factors such as the cooling rate during solidification of the weld pool [64][65][66].…”
Section: Microstructure and Xrd Measurementsmentioning
confidence: 99%
“…However, for a more detailed analysis, Figure 8a shows the microstructure at the interface for coating C1, highlighting the presence of martensite and austenite. Prior research has found that high Ni and Mo content stabilizes austenite during solidification, leading to the formation of austenite [63]. Martensite formation at the interface zone is attributed to factors such as the cooling rate during solidification of the weld pool [64][65][66].…”
Section: Microstructure and Xrd Measurementsmentioning
confidence: 99%
“…The automobile, electronics, aerospace, energy, defense, and other diverse industries all rely on hot work molds [1][2][3][4]. Hot work molds are susceptible to wear, corrosion, and fatigue cracking as a result of their highly complex processing, lengthy production cycles, and high costs [5][6][7]. Businesses will suffer significant financial losses and contribute significantly to industrial resource waste if the failed molds are immediately thrown away.…”
Section: Introductionmentioning
confidence: 99%